Workability of the sapphire crystal of medical purpose and scheme of formation of spherical surface ofincreased precision - Turmanidze, R. S.; Butskhrikidze, D. S.; Beridze, M. D. (НТУ "ХПИ", 2011)
Problems connected with the definition of influence degree of orientation of sapphire crystal on its machinability during diamond grinding by disc face and elaboration of the perspective, original scheme of formation of the incomplete spherical surface, particularly, sapphire head of endo-prosthesis of the human hip joint are considered.

Рассмотрены проблемы взаимосвязи степени влияния ориентации кристалла сапфира с его обрабатываемостью во время алмазного шлифования, также разработана перспективная оригинальная схема формообразования неполной сферической поверхности, особенно, сапфировая головка эндопротеза человеческого бедренного сустава.
Технологичность кристаллического сапфира медицинского назначения и схема формирования сферической поверхности повышенной точности
Keywords: endo-prosthesis; diamond grinding; human hip joint; алмазное шлифование; эндопротез; человеческий бедренный сустав